Practice effects predict cognitive outcome in amnestic Mild Cognitive Impairment - Duff, Kevin (2011)
OBJECTIVE: Practice effects on cognitive tests have been shown to further characterize patients with amnestic Mild Cognitive Impairment (aMCI), and may provide predictive information about cognitive change across time. We tested the hypothesis that a loss of practice effects would portend a worse prognosis in aMCI. DESIGN: Longitudinal, observational design following participants across one year. SETTING: Community-based cohort. PARTICIPANTS: Three groups of older adults: 1. cognitively intact (n=57), 2. aMCI with large practice effects across one week (MCI+PE, n=25), and 3. aMCI with minimal practice effects across one week (MCI−PE, n=26). MEASUREMENTS: Neuropsychological tests. RESULTS: After controlling for age and baseline cognitive differences, the MCI−PE group performed significantly worse than the other groups after one year on measures of immediate memory, delayed memory, language, and overall cognition. CONCLUSIONS: Although these results need to be replicated in larger samples, the loss of short-term practice effects portends a worse prognosis in patients with aMCI.